Women in forensic settings - McLeod, David Axlyn (Handbook of forensic social work, 2024)
The ways the criminal justice system interacts with women are distinctly different from men. To provide competent services to these women, forensic social workers must take explicit account of these differences. Often, women who experience crime and victimization choose not to interact with the system at all. This chapter will cover the specifics of gender inequalities and women’s experiences across multiple facets of survivorship, the differential nature by which they interact with the criminal justice system, and the social and political realities that drive these circumstances. Intersectionality and the complexities of women’s experiences will be examined and theoretical and pragmatic approaches to remedying some of these challenges provided.